Rencana Tahapan Penambangan Batubara Pada Tambang Terbuka Di Pit Selatan PT. RPP Contractor Indonesia Kecamatan Loa Janan Kabupaten Kutai Kartanegara Kalimantan Timur - Fauzan Dwi Syahputra; Shalaho Dina Devy; Henny Magdalena (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
In mining activities, especially in coal mining, of course there is a plan/design in mining activities that will be carried out such as production scheduling, fleet determination, to monthly/annual mining design stages. At PT.RPP Contractors Indonesia (RCI), precisely in the north pit, it has a production target that has been set, so it is necessary to phase out the mining plan to increase the planned production level and also to divide the entire volume in the pit limit into planning units that are smaller and easier to handle. To design a mining activity that will be carried out at PT.RPP Contractors Indonesia in making mining stages by making effective working hours or Standard Operational Parameters (SPO), determining the units to be used in mining activities, determining the fleet system and monthly design/ annual. The method used in making the mining phasing design is by making a block model for the bondary pit design and making schdulling stages in the software to facilitate the achievement of the production targets to be set. The results of the research resulted in mining stages in the Shorterm period (Quarterly) with estimated reserves of Overburden 713.000 BCM dan Coal 146.000 MT. Januari 203.917 BCM/44.500 MT, Februari 234.000 BCM/48.000 MT, Maret 265.000 BCM/54.000 MT with work units used 3 units of Excacvators and HD/dump trucks for OB removal and coal getting processes. With a 3 fleet system for stripping Overburden and Coal getting.